Maternal body mass index in early pregnancy and offspring asthma, rhinitis and eczema up to 16 years of age. Issue 1 (January 2015) - Ekström, S.; Magnusson, J.; Kull, I.; Lind, T.; Almqvist, C.; Melén, E.; Bergström, A.
Summary Background Maternal obesity has been linked to offspring asthma; however, other allergy‐related diseases, as well as the association beyond early school age, are largely unstudied. Objective To examine the associations between maternal body mass index (BMI) in pregnancy and offspring asthma, rhinitis, eczema and sensitization up to 16 years of age. Methods A total of 3294 children from the Swedish birth cohort BAMSE were included in the analyses. Maternal BMI was assessed around week 10 in pregnancy. Information on asthma, rhinitis, eczema, lifestyle factors and environmental exposures was obtained by parental questionnaires at 1, 2, 4, 8, 12 and 16 years. Sensitization was defined from IgE levels of inhalant allergens at 4, 8 and 16 years in a subsample of 2850 children. Generalized estimated equation models were used to analyse the associations between maternal BMI and the outcomes at 1–16 years. Results Maternal BMI was positively associated with overall risk of asthma up to age of 16 years (adj OR per 5 kg/m2 increase: 1.23; 95% CI 1.07–1.40 for prevalent asthma) excluding underweight mothers. In contrast, no significant associations were found for rhinitis, eczema or sensitization. The association with asthma was restricted to obese, rather than overweight mothers, but was attenuated when adjusting for overweight in the offspring. A causal inference test at 16 years further indicated that the child's own overweight is a mediator in the suggested association between maternal BMI and offspring asthma at 16 years. Conclusions and Clinical Relevance Maternal BMI is associated with an increased risk of asthma, but not rhinitis, eczema or sensitization; however, overweight in the offspring seems to have a mediating role. Prevention strategies of maternal pre‐pregnancy and childhood obesity might be important to reduce the prevalence of childhood asthma.